Erythropoietin-driven signaling ameliorates the survival defect of DMT1-mutant erythroid progenitors and erythroblasts - Horvathova, Monika; Kapralova, Katarina; Zidova, Zuzana; Dolezal, Dalibor; Pospisilova, Dagmar; Divoky, Vladimir (Haematologica, 2012)
BACKGROUND: Hypochromic microcytic anemia associated with ineffective erythropoiesis caused by recessive mutations in divalent metal transporter 1 (DMT1) can be improved with high-dose erythropoietin supplementation. The aim of this study was to characterize and compare erythropoiesis in samples from a DMT1-mutant patient before and after treatment with erythropoietin, as well as in a mouse model with a DMT1 mutation, the mk/mk mice. DESIGN AND METHODS: Colony assays were used to compare the in vitro growth of pre-treatment and post-treatment erythroid progenitors in a DMT1-mutant patient. To enable a comparison with human data, high doses of erythropoietin were administered to mk/mk mice. The apoptotic status of erythroblasts, the expression of anti-apoptotic proteins, and the key components of the bone marrow-hepcidin axis were evaluated. RESULTS: Erythropoietin therapy in vivo or the addition of a broad-spectrum caspase inhibitor in vitro significantly improved the growth of human DMT1-mutant erythroid progenitors. A decreased number of apoptotic erythroblasts was detected in the patient's bone marrow after erythropoietin treatment. In mk/mk mice, erythropoietin administration increased activation of signal transducer and activator of transcription 5 (STAT5) and reduced apoptosis in bone marrow and spleen erythroblasts. mk/mk mice propagated on the 129S6/SvEvTac background resembled DMT1-mutant patients in having increased plasma iron but differed by having functional iron deficiency after erythropoietin administration. Co-regulation of hepcidin and growth differentiation factor 15 (GDF15) levels was observed in mk/mk mice but not in the patient. CONCLUSIONS: Erythropoietin inhibits apoptosis of DMT1-mutant erythroid progenitors and differentiating erythroblasts. Ineffective erythropoiesis associated with defective erythroid iron utilization due to DMT1 mutations has specific biological and clinical features.
Keywords: kationické antimikrobiální peptidy; železo; Cell Survival; signální transdukce; Signal Transduction; Apoptosis; Erythroid Precursor Cells; Bone Marrow; proteiny přenášející kationty; Humans; Iron; Cation Transport Proteins; erythropoetin; kaspasy; Erythroblasts; mutace; Anemia, Hypochromic; hepcidiny; erytroblasty; lidé; Erythropoietin; zvířata; Caspases; myši; Hepcidins; erytrocytární znaky; Antimicrobial Cationic Peptides; Mice; apoptóza; erytroidní prekurzorové buňky; myši knockoutované; Mice, Knockout; Erythrocyte Indices; kostní dřeň; Animals; Mutation; viabilita buněk; hypochromní anemie